Participatory Communication in Children’s Communities for Preventing Child Marriage after the COVID-19 Pandemic in Sukabumi - Sri Utami, Yessi (UPT Publikasi Ilmiah UNISBA, 2024)
The high rate of child marriage cases in Sukabumi Regency following the COVID-19 pandemic has encouraged the children’s community in Sukabumi to form unique cooperation with the government. This research aims to analyze the participatory communication between the child community and the government in preventing child marriage and achieving Sustainable Development Goals (SDGs) after the COVID-19 pandemic in Sukabumi, West Java. The research employs a qualitative method with a case study approach, analyzing several children’s communities. Data collection was conducted using multiple sources, including observation, interviews, and documentation studies. This research shows that participatory communication within the children’s community enhances adolescent agency communally through dialogue, heteroglossia, polyphony, and carnival. Dialogue was found to be the dominant form and plays a major role in realizing effective communication. Children’s communities used both digital and face-to-face media to achieve resilience and build participation during the COVID-19 pandemic, with face-to-face media being more dominant in interactions with the government. This study found that participatory communication increases collaboration between the children’s community and the government, contributing to the reduction of child marriage in Sukabumi.